2012
DOI: 10.1016/j.ypmed.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated chronic diseases require age-old medicine: Role of chronic inflammation

Abstract: Most chronic diseases - such as cancer, cardiovascular disease (CVD), Alzheimer disease, Parkinson disease, arthritis, diabetes and obesity - are becoming leading causes of disability and death all over the world. Some of the most common causes of these age-associated chronic diseases are lack of physical activity, poor nutrition, tobacco use, and excessive alcohol consumption. All the risk factors linked to these chronic diseases have been shown to up-regulate inflammation. Therefore, downregulation of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(178 citation statements)
references
References 115 publications
(114 reference statements)
1
170
0
7
Order By: Relevance
“…Our results are similar to other studies conducted in near regions. These results could be explained first by the relationship existing between age progressing and chronic diseases [22][23][24][25]. Second, people more than 50 years old have more knowledge to use MPs than young people; such knowledge is usually acquired following a long experience and transmission from one generation to another [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to other studies conducted in near regions. These results could be explained first by the relationship existing between age progressing and chronic diseases [22][23][24][25]. Second, people more than 50 years old have more knowledge to use MPs than young people; such knowledge is usually acquired following a long experience and transmission from one generation to another [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus increasing physical activity may reduce the risk of Alzheimer's disease by lowering chronic inflammation. 91 The effect of the Apolipoprotein E ε4 allele…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…In fact, most chronic diseases are dependent upon chronic inflammation as a key factor in their development and/or maintenance [91]. Additionally, Prasad et al [92] argue that all risk factors of chronic diseases up-regulate inflammation. The problem is so pervasive and extensive that Aller et al [93] suggested that inflammation problems have the potential to exert an evolutionary impact.…”
Section: Misregulated Inflammation Is the Root Of Most Chronic Diseasesmentioning
confidence: 99%